THE INFLUENCE OF STORE ATMOSPHERE ON CONSUMER PURCHASE DECISION AT KAWAN BARU RESTAURANT MEGA MAS MANADO - Waloejan, Nia Anggreini (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Culinary business is a business type that’s growing rapidly in the city of Manado. Nowadays, a taste of food, price, services and quality of the foods no longer being a major consideration for the culinary connoisseur. The store atmosphere becomes an important factor for consumers to choosing a place for dine. The research aim to analyzing the influence of store atmosphere on Kawan Baru Restaurant Mega Mas Manado. The analytical methods of analysis used by multiple linear regression analysis techniques. The data used in this research is primary data obtained through the questionnaire distributed to consumer Kawan Baru Restauran Mega Mas Manado. Based on the analysis the results are store exterior, general interior, store layout and interior display significantly influence consumer’s purchase decision on Kawan Baru Restaurant Mega Mas Manado. Based on the results of this research, the restaurant management should be more understanding of the marketing strategy related to the restaurant atmosphere and the benefits that accrue when the atmospheric restaurant can impress consumers, this increasing satisfaction and intentions consumer behavior. Keywords: store atmosphere, consumer purchase decision